A new method for assessing the application of deterministic or stochastic modelling approach in evacuation scenarios - Alvear, D.; Abreu, O.; Cuesta, A.; Alonso, V. (Fire safety journal, 2014)
The utilisation and importance of evacuation simulation models have grown due to their capabilities in the prevention, management and subsequent analysis of emergencies, and their contribution to protecting human life. Although several evacuation models for different types of scenarios exist in the field of fire safety engineering, it should be noted that most of these employ a deterministic approach. However, the evacuation process is a highly random phenomenon that is subject to the variability of human behaviours and other risk factors pertaining to an emergency. This paper studies the effect of using a deterministic instead of a stochastic approach in evacuation modelling. In this sense, two methods are proposed: (1) an exact method, which analyses the relative error when a deterministic approach is used and also offers acceptance or rejection criteria and (2) an a priori method, which predicts when a deterministic approach can be accepted or rejected by considering the independent variable characteristics of the corresponding model. Both methods are applied to two evacuation scenarios: 1) passenger trains and 2) road tunnels. These application cases show the usefulness of these two methods. Furthermore, this paper shows the necessity of continuing to study the influence of diverse factors in deterministic or stochastic modelling for evacuation analysis. • The impact of using a deterministic approach in evacuation modelling is analysed.• The exact method quantifies the relative error when using a deterministic approach.• A priori method is based on the level of randomness of independent inputs.• A stochastic approach for passenger trains and road tunnels is required.